The ‘Air of Liberty’. Narratives of the South Atlantic Past - Stecher, Lucía (Meridional. Revista Chilena de Estudios Latinoamericanos, 2013)
Ineke Phaf-Rheinberger Amsterdam-New York: Rodopi. Cross/Cultures Series, 2008